Reforming International Trade Law to Support Developing Countries: A Study on Fairness, Access, And Sustainable Growth - Dilshika Thilakarathne, W.V.A.T. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
The evolving landscape of international trade law presents both challenges and opportunities for developing countries seeking equitable participation in the global market. This study critically examines the current frameworks of international trade law, highlighting their implications for fairness, access, and sustainable growth among developing nations. Through a comprehensive analysis of existing legal structures, including the World Trade Organization (WTO) agreements and regional trade pacts, this research underscores the systemic inequities often encountered by less developed economies. Key findings illustrate that traditional trade laws frequently prioritize the interests of developed countries, inadvertently marginalizing developing nations and limiting their economic potential. This study advocates for a reformative approach, proposing specific amendments to international trade regulations that prioritize inclusivity and equitable access to markets. By analyzing case studies and empirical data, the research emphasizes the necessity of integrating sustainability principles into trade law to foster long-term economic resilience and environmental stewardship in developing regions. Furthermore, the study explores the role of innovation in trade facilitation, arguing that technology transfer and capacity-building initiatives are essential for empowering developing countries to navigate and leverage global trade dynamics effectively. In conclusion, this research calls for a redefined international trade law framework that not only promotes fairness and equitable access for developing countries but also emphasizes sustainable growth as a critical criterion for future trade agreements. By addressing these vital areas, the study aims to contribute to the dialogue on international economic governance, highlighting the essential role of developing countries in shaping a more just and sustainable global trading system.
Keywords: International trade law; Developing countries; Fairness; Market access; Sustainable growth